MANAGEMENTUL ACTIVITĂȚII TURISTICE ÎN RAPORT CU COMPONENTELE SISTEMULUI INFORMAȚONAL CONTABIL - Costețchi-Jușca, Oxana (CEP USM, 2020)
Being an economic activity that involves a certain way of organizing and deploying, based on training and resource utilization, and achieving results, tourism is objectively subject to a managerial process. Elaborating correct and timely decisions is only possible if the leadership of an economic entity has sufficient information about the problems and phenomena that it faces. In other words, efficient and modern management implies the existence of an efficient information system capable of providing management with all the necessary elements for the decision-making process. Within the global information system of an economic entity, a major role is played by the accounting information subsystem, which is the basic tool of activity management, especially in tourism activity, which due to its specific nature requires a continuous and intense processing of data and information by financial and management accounting.
Keywords: management accounting; financial accounting; accounting information; management; tourism